Howard Robinson and the “British Method”: A Case Study of Britishness in Canada during the 1930s and 1940s - Nerbas, Don (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2009)
AbstractDuring the 1930s and 1940s economic crisis and world war in Canada worked to erode the persistent ideological claim that government best played a largely hands-off role in social and economic life. For Howard P. Robinson (1874–1950), a Saint John, New Brunswick, newspaper owner and capitalist, this trend was part of a broader challenge to what he believed was the British tradition in Canada. Subscribing to a sense of Britishness that was both racialist and imperialist, he believed the strict maintenance of social order and laissez-faire philosophy to be key aspects of the British tradition. Increasingly, however, the rising tide of social democracy and economic and cultural integration with the United States made Robinson’s worldview anachronistic within the outlook of the Canadian bourgeoisie. Robinson’s position was not without its contradictions, but his enduring sense of Britishness provides an archetypal case study of the mentalité of a conservative member of Canada’s economic élite during a time of significant changes.